2009
DOI: 10.1242/dev.034439
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of BMP signaling on parvalbumin and somatostatin interneuron differentiation

Abstract: +interneurons. PV + interneurons in the cortex express BMP type I receptors and a subpopulation displays activated BMP signaling, assessed by downstream molecules including phosphorylated SMAD1/5/8. Conditional mutation of BMP type I receptors in interneuron precursors significantly reduces the number of cortical PV + interneurons in the adult brain. Thus, BMP4 signaling through type I receptors regulates the differentiation of two major medial ganglionic eminence-derived interneuron populations and defines th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 58 publications
(78 reference statements)
3
48
0
Order By: Relevance
“…Another gene purported to be highly expressed in the OB, ferritin (Connor et al , 1990) showed little response to CPF, but was induced on exposure to Cu alone, and also by the Cu/CPF mixtures (Figure 4B). The pvalb8 protein is important in maintaining calcium ion balance in neuronal cells (Mukhopadhyay et al , 2009). As observed in figure 5B, expression of the pvalb8 transcript was impacted by CPF, but was much more repressed in the presence of Cu.…”
Section: Resultsmentioning
confidence: 99%
“…Another gene purported to be highly expressed in the OB, ferritin (Connor et al , 1990) showed little response to CPF, but was induced on exposure to Cu alone, and also by the Cu/CPF mixtures (Figure 4B). The pvalb8 protein is important in maintaining calcium ion balance in neuronal cells (Mukhopadhyay et al , 2009). As observed in figure 5B, expression of the pvalb8 transcript was impacted by CPF, but was much more repressed in the presence of Cu.…”
Section: Resultsmentioning
confidence: 99%
“…We found that both types of GABAergic neurons are present at 4M, which indicates that our differentiation protocol generates GABAergic neurons of mixed subtypes. It is possible that an additional step involving the treatment of the differentiating cells with a factor such as BMP4 would lead to a more homogeneous population of GABAergic interneurons expressing PV (Mukhopadhyay et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…This is evident in the greater number of GABAergic interneurons that are derived from progenitor cells in the dorsolateral versus the dorsomedial wall of the telencephalon, where BMP expression is highest (Furuta et al 1997;Mehler et al 1997;Grove et al 1998). Exogenous Shh expression in the dorsomedial wall enhances the number of GABAergic interneurons (Gulacsi and Lillien 2003), whereas BMP signaling determines the fate of GABAergic interneuron pre-cursors, promoting differentiation of parvalbumin-positive interneurons and blocking differentiation of calbindin-and somatostatinpositive interneurons (Samanta et al 2007;Mukhopadhyay et al 2009). Induction of basal forebrain cholinergic neurons (BFCNs) requires BMP-9 expression (LĂł pez-Coviella et al 2000,2005) and, interestingly, human embryonic stem-cell cultures confirm that BMP-9 induces expression of transcription factors that are necessary and sufficient for BFCN induction (Bissonnette et al 2011).…”
Section: Forebrainmentioning
confidence: 99%